PEMBUATAN KONEKTOR PADA BANGUNAN SIPIL YANG DIBANGUN DENGAN METODE SPLITTING HOUSE - Nopriyanti, Rani; Soetopo, Antonius Adi; Setiawan, Heri; Akbari, Rizqy Hikmat (STKIP PGRI Situbondo, 2025)
Civil buildings are structures built to meet human needs in infrastructure and the environment. This includes bridges, buildings, and more. The method used is the Splitting House method which is a term where the entire building or assembly components are manufactured off-site and assembled on-site from separate panel modules. The Splitting House method is used to overcome the relatively large dimensions of the 3DCP machine so that handling the machine to the work area becomes impractical. This method requires connectors to connect separate panels. The connector consists of a Connector L (275,25 mm x 138 mm x 2 mm) and a Connection Plate (140 mm x 140 mm x 2 mm). This connector can safely support the load, has a compressive voltage of 0.0195 Mpa and a clearance voltage of 122.5 Mpa. Weld potency reaches 18.03 (). The bolt joints have a shear capacity of 7.2 kN, bearing resistance of 5.1 kN, and tensile resistance of 8.7 kN. The manufacture of the connector takes 12.9 hours and costs Rp. 1.104.257,60.